Pelatihan Wordpress Dan Blogger Di SMKN 1 Sepulu - Luluk Mauli Diana; Meilia Intan Sabila (Lembaga Penjaminan Mutu Universitas Abdurachman Saleh Situbondo, 2026)
The development of information technology requires Vocational High School (SMK) students to have skills in creating and managing websites to support digital literacy and personal branding skills. However, conditions at SMKN 1 Sepulu show that students do not have an adequate understanding of creating websites such as WordPress and blogger. This activity aims to provide training in creating websites and blogs as an effort to increase students' digital competence. The implementation method includes the preparation stage, delivering material and practice, and evaluation. Training is carried out in the form of lectures, student practice and direct assistance to students in creating websites using WordPress and blogs via blogger. The results of the activity show that students are able to create a simple website, adjust the appearance, add pages, write articles, and publish content independently. Students look enthusiastic in developing displays and utilizing the available features. In addition, this training provides students with increased digital literacy, technical skills and understanding of personal branding. Therefore, this WordPress and blogger training is effective in improving the competency of SMKN 1 Sepulu students, especially in website and blog management skills that are relevant to the demands of the world of work.